Efektivitas Teknik Mingle Untuk Meningkatkan Kemampuan Membaca Permulaan bagi Anak Tunagrahita Ringan di SLBN 2 Padang - Elfia Yurmalina; Kasiyati Kasiyati (Universitas Negeri Padang, 2019)
ABSTRACTThis study discusses the problems found in SLB N 2 Padang, towards mild third-grade mentally retarded children who have difficulty in firts step of reading, such as reading simple words. This study aims to determine whether an effective mingle technique is used to improve the ability to firts step of reading in mild mentally retarded children. The research method used in this study was an experiment with a quasi-experimental approach. The study was conducted with two observations, namely before experiment (O1) called pre-test and after experiment (O2) called post-test. The research data analysis technique was carried out by the Mann Whitney test with a significant level of 95% and α = 0.05. Based on the results of data analysis in the pre-test and post-test showed an increase in the ability to firts step of reading. Pre-test with an average of 13.3% and post-test 94%. The calculation results obtained by Uhitung = 15 and Utabel = 7. Based on the hypothesis testing Ha is accepted with Uhit≥Utab. Based on the results of the analysis of the data shows that the effective mingle technique is used to improve the ability to firts step of reading for mild mentally retarded children.ABSTRAKPenelitian ini membahas tentang permasalahan yang ditemukan di SLB N 2 Padang, terhadap anak tunagrahita ringan kelas III yang mengalami kesulitan dalam membaca permulaan, seperti membaca kata sederhana. Penelitian ini bertujuan untuk mengungkapkan apakah teknik mingle efektif digunakan untuk meningkatkan kemampuan membaca permulaan pada anak tunagrahita ringan. Metode penelitian yang digunakan dalam penelitian ini adalah eksperiment dengan pendekatan quasi eksperiment. Penelitian dilakukan dengan dua kali observasi yaitu sebelum eskperimen (O1) disebut pre-test dan sesudah eksperimen (O2) disebut post-test. Teknik analisis data penelitian dengan uji Mann Whitney dengan taraf signifikan 95% dan α = 0,05. Berdasarkan hasil analisis data dalam pre-test dan post-test menunjukkan peningkatan kemampuan membaca permulaan. Pre-test dengan rata-rata 13,3% dan post-test 94%. Hasil perhitungan diperoleh Uhitung=15 dan Utabel=7. Berdasarkan pengujian hipotesis Ha diterima dengan Uhit≥Utab. Berdasarkan hasil analisi data tersebut menunjukkan bahwa teknik mingle efektif digunakan untuk meningkatkan kemampuan membaca permulaan bagi anak tunagrahita ringan.